New Cartographies of Hispanism: From Spanish to Iberian literary history? - Pérez Isasi, Santiago (2018)
It is not my intention to imagine a parallel universe in which literary history and national identity were not so strongly intertwined from the beginning; we should not forget that this impulse to promote the knowledge of national literatures paved the way for the rediscovery of literary productions which were forgotten or underrated by previous classical standards. What I would like to show in the following pages is, firstly, that this national model of literary history relies on an implicit conception of the linguistic and cultural territory that promotes and celebrates homogeneity and erases difference; that in doing so it forgets and underrates other literary phenomena which do not respond well to the homogeneous conception of the nation; and in the last section, I will propose an alternative model for national literary history, which still has not had the development it probably merits: a non-national, non-teleological version of Iberian literary history, based on the idea of ‘cultural polysystems’, following the most recent publications in the field of Iberian Studies.